Dietary oil palm (Elaies guineensis Jacq.) frond supplementation can alter plasma lipoprotein concentrations in goats - Ebrahimi, Mahdi; Rajion, Mohamed Ali; Goh, Yong Meng; Sazili, Awis Qurni (2011)
Twenty four six-month old Kacang crossbred goats were allocated into three treatment groups and fed a control (CON; 100% concentrate), HAF (75% concentrate + 25% oil palm frond pellet, % w/w) or OPF 950% concentrate + 50% oil palm frond pellet, %w/w) diet for 100 days. The plasma lipoprotein profiles from these animals were compared. Results showed the OPF and HAF goats had significantly higher (P<0.05) plasma HDL-cholestrol values compared to the CON animals. However there were no significant (P>0.05) differences in plasma total cholestrol, LDL-cholestrol and triaglycerols between the treatment groups. This study showed that the ‘good’ plasma HDL-cholestrol in goats was increased by the oil palm frond supplementation.